Nationwide implementation of the international multidisciplinary best-practice for locally advanced pancreatic cancer (PREOPANC-4): study protocol - Stoop, Thomas F.; Seelen, L. W. F.; Land, F. R. van 't; Hout, A. C. van der; Scheepens, J. C. M.; Ali, M.; Stiggelbout, A. M.; Kolk, B. M. van der; Bonsing, B. A.; Lips, D. J.; Groot, D. J. A. de; Veldhuisen, E. van; et al. (BMC cancer, 2025)
The introduction of (m)FOLFIRINOX and gemcitabine-nab-paclitaxel has changed the perspective for patients with locally advanced pancreatic cancer (LAPC). Consequently, in experienced centres 23% of patients with LAPC undergo a resection with 5-year overall survival (OS) rates of up to 25%. In the Netherlands, the nationwide resection rate for LAPC remains low at 8%. The PREOPANC-4 program aims for a nationwide implementation of the international multidisciplinary best-practice to improve patient outcome.